PD-1 inhibition disrupts collagen homeostasis and aggravates cardiac dysfunction through endothelial-fibroblast crosstalk and EndMT - Zhang, Zejin; Yan, Zhenzhen; Yuan, Tao; Zhao, Xiaona; Wang, Minghui; Liu, Guoqing; Gan, Lijun; Qin, Wei (Frontiers in Pharmacology, 2025)
IntroductionCardiac immune-related adverse events (irAEs) from PD-1-targeting immune check-point inhibitors (ICIs) are an increasing concern due to their high mortality rate. Collagen plays a crucial role in maintaining cardiac structure, elasticity, and signal transduction; however, the effects and mechanisms of PD-1 inhibitor on cardiac collagen remodeling remain poorly understood.MethodsC57BL/6 mice were injected with anti-mouse PD-1 antibody to create a PD-1 inhibitor-treated model. Cardiac function was measured by echocardiography, and collagen distribution was analyzed with Masson’s trichrome staining and Sirius Red staining. Single-nucleus RNA sequencing was performed to examine the effects of PD-1 inhibition on gene expression in cardiac fibroblasts (CFs) and endothelial cells (ECs). EC-CF crosstalk was assessed using co-culture experiments and ELISA. ChIP assay was performed to analyze the regulation of TCF12 on TGF-β1 promoter. Western blot, qRT-PCR, and immunofluorescence staining were used to detect the expression of TCF12, TGF-β1, and endothelial-to-mesenchymal transition (EndMT) markers. Reactive oxygen species (ROS) levels were evaluated by DHE staining, MDA content, and SOD activity assays.ResultsWe report a newly discovered cardiotoxic effect of PD-1 inhibitor, which causes aberrant collagen distribution in the heart, marked by a decrease in interstitial collagen and an increase in perivascular collagen deposition. Mechanistically, PD-1 inhibitor does not directly affect CFs but instead impact them through EC-CF crosstalk. PD-1 inhibitor reduces TGF-β1 secretion in ECs by downregulating TCF12, which we identify as a transcriptional promoter of TGF-β1. This subsequently decreases CF activity, leading to reduced interstitial collagen deposition. Additionally, PD-1 inhibitor induces EndMT, increasing perivascular collagen deposition. The endothelial dysfunction induced by PD-1 inhibitor results from ROS accumulation in ECs. Inhibiting ROS with N-acetylcysteine (NAC) preserves normal collagen distribution and cardiac function in PD-1 inhibitor-treated mice by reversing TCF12 downregulation and EndMT in ECs.ConclusionOur results suggest that PD-1 inhibitor causes ROS accumulation in cardiac ECs, leading to imbalanced collagen distribution (decrease in interstitial collagen and increase in perivascular collagen) in the heart by modulating TCF12/TGF-β1-mediated EC-CF crosstalk and EndMT. NAC supplementation could be an effective clinical strategy to mitigate PD-1 inhibitor-induced imbalanced collagen distribution and cardiac dysfunction.